Rain Induced Cross Polarization on Satellite Communication in Nigeria (Journal of Informatics and Mathematical Sciences, 2017)
Microwave systems performance on satellite communication link operating above 10 GHz is increasingly degraded by rain when designing telecommunication systems. Cross polarization is one of the major source of signal degradation that affectthe frequency reuse when employed to boost capacity of the channel. The effect of cross-polarization in thirty-seven (37) stations in Nigeria were carried out using 10 years data obtained from Nigeria Meteorological Agency (NIMET) at the look angle from Nigeria Communication Satellite (NigComSat). International Telecommunication Union-Recommendation (ITU-R) model was used to for this study. The stations were grouped into six geopolitical zones in Nigeria which are Southwest (SW), Southeast (SE), South-south (SS), Northcentral (NC), Northwest (NW) and Northeast (NE). The results reveal that cross-polarization discrimination (XPD) become very poor as frequency (at Ku-band, Ka-band, V-band) increases especially at lower percentage of time (such as 0.001%, and 0.01%) unavailability. Hence XPD, at all frequencies is poorer in the southern part of Nigeria SE, SS and SW due to high rainfall rate. The results also show that only Northern part of the country will experience no interference at 0.01% as XPD is over 30 dB ITU-R base line for Ku-band transmission. However, for Ka-band and V-band at 0.001% and 0.01% unavailability of time interference will occur in all stations in Nigeria, but at 0.1% and 1% XPD is over 30 dB for all stations. This study will help in the adequate planning and designing of satellite telecommunication expansion in all the six geopolitical zones in Nigeria.
Keywords: Cross-polarization discrimination; Satellite communication; Frequency; Rainfall rate